Coordinated Membrane Ballooning and Procoagulant Spreading in Human Platelets. Issue 15 (13th October 2015) - Agbani, Ejaife O.; van den Bosch, Marion T.J.; Brown, Ed; Williams, Christopher M.; Mattheij, Nadine J.A.; Cosemans, Judith M.E.M; Collins, Peter W.; Heemskerk, Johan W.M.; Hers, Ingeborg; Poole, Alastair W.
Abstract : Background—: Platelets are central to the process of hemostasis, rapidly aggregating at sites of blood vessel injury and acting as coagulation nidus sites. On interaction with the subendothelial matrix, platelets are transformed into balloonlike structures as part of the hemostatic response. It remains unclear, however, how and why platelets generate these structures. We set out to determine the physiological relevance and cellular and molecular mechanisms underlying platelet membrane ballooning. Methods and Results—: Using 4-dimensional live-cell imaging and electron microscopy, we show that human platelets adherent to collagen are transformed into phosphatidylserine-exposing balloonlike structures with expansive macro/microvesiculate contact surfaces, by a process that we termed procoagulant spreading. We reveal that ballooning is mechanistically and structurally distinct from membrane blebbing and involves disruption to the platelet microtubule cytoskeleton and inflation through fluid entry. Unlike blebbing, procoagulant ballooning is irreversible and a consequence of Na +, Cl –, and water entry. Furthermore, membrane ballooning correlated with microparticle generation. Inhibition of Na +, Cl –, or water entry impaired ballooning, procoagulant spreading, and microparticle generation, and it also diminished local thrombin generation. Human Scott syndrome platelets, which lack expression of Ano-6, also showed a marked reduction in membrane ballooning, consistent with a role for chloride entry in the process. Finally, the blockade of water entry by acetazolamide attenuated ballooning in vitro and markedly suppressed thrombus formation in vivo in a mouse model of thrombosis. Conclusions—: Ballooning and procoagulant spreading of platelets are driven by fluid entry into the cells, and are important for the amplification of localized coagulation in thrombosis. Abstract : Supplemental Digital Content is available in the text.